SISTEM MONITORING PEMERATAAN SUHU PADA INKUBATOR TELUR BERBASIS NODE MCU - Zaenal Arifin; Dias Prihatmoko; Safrizal Safrizal; Saharul Alim; Nazar Choir (Jurnal Disprotek, 2023)
The development of tools that are increasingly modern from time to time where one of them is a poultry egg incubator, temperature is a major factor in hatching poultry eggs, the market demand is greater than production. By taking advantage of technological developments, breeders can use egg incubators. The purpose of this tool is to create temperature control in the box that is evenly distributed in the poultry egg incubator so that hatching success is higher. The method used is development by searching for material, designing tools and then making egg incubators with size (50x40x50) cm, and installing four Dht-11 sensors at each corner of the incubator, data collection to analysis. Testing the DHT-11 sensor at a setting point of 38oC from the four sensors, during the daytime test it takes 10 minutes to reach a temperature of 38oC from the four sensors, and the temperature is stable in the range of 37oC-39oC. The results of this study are in the form of testing the DHT-11 sensor at night, it takes 12 minutes for the four sensors to reach the setting point of 38oC, from testing for one hour with data collection every two minutes the temperature is stable in the range of 37oC-39oC from the four sensors installed on the four corners of the rack on the egg incubator. Tests of ultrasonic sensors one and two get readings if the distance is less than 40 cm then the buzzer will light up. Telegram testing results where the temperature status in the egg incubator box can be accessed at any time.